Accountant as a career choice from the perspective of secondary school and undergraduate accounting students in Malaysia - Muhamad, Haslinah; Ong, Tze San; Soh, Wei Ni; Safingi, Aliffatur Radiah (Human Resource Management Academic Research Society, 2020)
This study examines the perception of accounting students in Malaysia towards the accounting profession and whether these perceptions are influenced by the gender and student categories (secondary school and undergraduates). This study was a cross-sectional survey of 156 undergraduate accounting students from School of Business and Economics, Universiti Putra Malaysia (UPM) and 115 secondary school accounting students from Sekolah Agama Menengah Tinggi Tengku Ampuan Rahimah (SAMTTAR). A self-administered structured questionnaire was developed to collect primary data. Data were analyzed using descriptive statistics such as mean, and Mann-Whitney test through SPSS 22. The results of this study show that, generally, female respondents have higher perception on accounting job requirement and reputation compare to male respondents. Additionally, undergraduate students have a higher perception on the accounting job requirement and negative behaviour of accountant compare to secondary school student. This research contributes to the academic debate surrounding the concerns of the future of accounting profession. It also provides an idea to the accounting regulatory body, professional accounting bodies, and educators as well other stakeholders to look on the job requirement and improvement on the negative image of accountant for the benefit of the profession in Malaysia.